(untitled) (Bangladesh Journal of Agricultural Research, 2013)
Mustard (Brassica juncea L.) production in India suffers from aphid, Lipaphis erysimi (Kaltenbach), infestation considerably. Role of weather on the incidence and development of mustard aphids was assessed from experimental data from six north Indian locations. Aphid appearance and population build up was found to be regulated by temperature and time to attain peak population was relatively short in warm humid climates than in cool climates. Aphids appeared generally when the accumulated thermal time ranged between 810-847 and diurnal temperature range had a key role on the pest build up. Functional relations developed from the present study between aphid incidence and peak population using previous weeks weather and pest data for majority of the locations could be used for taking of any prophylactic/control measures. Projections on aphid population in future climates using generated weather variables indicated that warming may not increase aphid population at all locations uniformly. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16924 Bangladesh J. Agril. Res. 38(3): 373-387, September 2013